The Role Of Teachers In Embedding Islamic Values And Ethics In Education: A Literature Review - Siti Suhaila Ihwani; Muhammad Talhah Ajmain @ Jima'ain; Zetty Nurzuliana Rashed (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
The purpose of this paper is to investigate the role of teachers in embedding Islamic values and ethics in education. The rationale of this study is by understanding how Islamic Education teachers should play their roles in embedding Islamic values and ethics, could perhaps contribute to better ways of students’ behavior development. In this regard, the study has focused on exploring how the roles of  Islamic Education teachers, and the challenges that affect the teachers in promoting Islamic values and ethics in education. The study used a library research design. The data were collected from research articles published in either international or national accredited journals. The research findings show although the elements of Islamic values and ethics seem to be discussed in Islamic Education, students show low Islamic values and ethics in their behavior. The study recommends several approaches to improve the teaching of Islamic values and ethics in schools which include training for teachers to improve the methodology of teaching and providing teaching and learning facilities. It is also suggested that an open discussion is conducted between parents, teachers, students, policymakers, and religious leaders to develop a guideline on what should be included in the syllabus and how to cultivate Islamic values and ethics in education effectively.   Keywords: Role Of Teacher, Islamic Values, Ethics